Bleeding in Surgery - Segura, Carlos Andrés Salas; Medina, Myrna Sofía Hernández; Sixtos, Jaime Ricardo López; Ruiz, César Arcos; Sánchez, Morelos Adolfo García (British Journal of Healthcare and Medical Research, 2025)
Introduction: the main specialized functions of blood as tissue are transport, defense, coagulation, barometric and temperature regulation. Objective: to describe the experience of patients bleeding in surgical diseases. Method: a multicenter study with a retrospective, longitudinal, observational and descriptive design of the Surgery and Coloproctology Service in five second and third level health care hospitals. Results: of 241 patients with complete files where bleeding will be specified by phases of surgical treatment, 162 women (67%) and 79 men (33%). Range 18 to 97 years. Two surgical pathologies present preoperative hemorrhage: blunt trauma/projectile by firearm/sharp instrument both in the chest, abdomen, extremities or mixed, quantifying 25 /2,650 milliliters and the second the ruptured ectopic pregnancy. Discussion: hypovolemic shock due to hemorrhage is one of the main causes of death in trauma patients in prehospital settings. In cases of traumatic shock, early control of bleeding and effective volume replacement with blood products are strategies to save lives. Conclusions: the hemorrhage of patients in surgery in public surgical practice in Mexico is an object of oblivion for the administrative area of hospitals, due to the extreme lack of supplies or resources, as well as the lack of competence of the personnel of the rest of the surgical team, which determine practically heroic behaviors of the surgeon responsible for saving the patient’s life.